Adolescent sexual behaviour in Navrongo: Does family count? - Muindi, Kanyiva (My University, 2007)
In the face of diminishing traditional controls on adolescent sexual behaviour, parents are becoming the focal point of guidance on sexual issues. The main objective of the study is to establish if residing with one’s parents has any effect on one’s sexual behaviour among adolescents in the Kassena-Nankana District of Northern Ghana. A sample of 7056 adolescents aged between 10 and 24 years were interviewed between April and October 2003 while the 2004 household socio-economic data was used to generate a household wealth index. Females are less likely to have had sex (AOR 0.75; CI: 0.63; 0.88) and also less likely to initiate sex before age 16 (AOR 0.30; CI: 0.21; 0.43) compared to males. Living with one’s father only is associated with a 36% decrease in the likelihood of having had sex among males (AOR 0.64; CI: 0.42; 0.96) compared to living with both parents. Females living with neither parent were 76% more likely to have had sex than those living with both parents (AOR 1.76; CI: 1.21; 2.55). Discussion of sexual matters with parents increased the likelihood of initiating sex. Family structure is an important predictor of sexual behaviour among adolescents and therefore should be considered when designing and implementing interventions. Longitudinal and qualitative studies are recommended
Student Number: 0516329A - MSc research report - School of Public Health - Faculty of Medicine
Keywords: adolescent; sexual behaviour; residing; parents; Kassena-Nankana District; Northern Ghana; sexual matters; discussion